1993
DOI: 10.1159/000213517
|View full text |Cite
|
Sign up to set email alerts
|

Natural Human Antibodies to Synthetic Peptide Autoantigens: Correlations with Age and Autoimmune Disease

Abstract: Clinically healthy humans as well as patients suffering from various autoimmune diseases produce natural antibodies against a variety of self-components. Such antibodies have been proposed to carry out a physiologic role in maintaining the integrity of self, as well as potentially destructive roles in the generation of autoimmune diseases. Because human autoantigens, particularly membrane proteins, are usually present in extremely small amounts, it is generally impossible to obtain enough to carry out a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…There is a constitutive autoimmunity in healthy individuals to immunoregulatory segments of TCR (3 chain (13,14). The levels of autoantibodies with characteristic specificity for these V(3-CDR1, V(-FR3, and CP determinants are substantially increased after HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a constitutive autoimmunity in healthy individuals to immunoregulatory segments of TCR (3 chain (13,14). The levels of autoantibodies with characteristic specificity for these V(3-CDR1, V(-FR3, and CP determinants are substantially increased after HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that normal humans (13) and individuals suffering from autoimmune diseases (14,15) can have elevated levels of autoantibodies directed against peptide determinants forming putative immunoregulatory sites on the V domains making up complementarity-determining region (CDR) 1, framework region (FR) 3, and a region of the constant (C) domain. Studies with mice show that these types of autoantibodies are generated after experimentally induced infection with retrovirus (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14-16 A prevalence of anti-TCR antibodies, however, has been reported in conditions such as ageing, 17,18 pregnancy, 19 allograft transplantation, 20,21 retroviral infections, 22,23 and autoimmune diseases. 14,15,17,18 It has been proposed that NAAbs against the TCR may serve in immunoregulation of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of autoantibodies directed against peptide defined epitopes of the T-cell receptor (TCR) b chain in normal sera and various physiological and disease states has been established in our laboratory using synthetic overlapping peptides and subsequent synthetic peptide epitope homologue analysis [1][2][3][4]. Initially, 22 nested synthetic 16-mer peptides were synthesized with five residue overlaps in order to mimic the covalent structure of the TCR b chain for epitope mapping studies of the Bence-Jones protein Mcg (l light chain: see [5]) and the YT35 TCR b gene product (TCR Vb8.1 human: see Refs 1,4 and 6).…”
Section: Introductionmentioning
confidence: 99%